Outcomes of Hindfoot and Ankle Arthrodesis in Neuropathic Patients - David Macknet MD; Andrew Wohler MD; Carroll P. Jones MD; J. Kent Ellington MD; Bruce E. Cohen MD; Robert B. Anderson MD; W. Hodges Davis MD (Foot & Ankle Orthopaedics, 2019)
Category: Ankle Arthritis, Diabetes, Hindfoot Introduction/Purpose: Charcot neuropathy of the ankle and hindfoot is a progressive and destructive process that can lead to instability and ulceration resulting in significant morbidity which can end with amputation. The foot and ankle surgeon’s aim is to reconstruct the high risk foot with the creation of a stable plantigrade foot, while reducing the risk of ulceration and allowing the patient to mobilize in commercially available footwear. There are numerous techniques for the reconstruction of the neuropathic hindfoot, but the most utilized of these include multiplanar external fixation or internal fixation with a plate or intramedullary nail. It is our goal to further elucidate outcomes of Charcot patients undergoing corrective ankle and hindfoot fusion comparing internal versus external fixation. Methods: We retrospectively collected 377 patients undergoing hindfoot and ankle arthrodesis at our institution from 2006- 2017. 77 patients were identified that underwent arthrodesis for Charcot arthropathy, 56 of which met our inclusion and exclusion criteria. This included 47 who had internal fixation as their primary procedure and 9 patients who underwent external fixation with a multi-planar external fixator. Our median follow up time was 3.4 years (IQR .5 to 12.9). Preoperatively we collected basic demographic variables, reasons for neuropathy, and ulcer status. Postoperatively we collected complications including infection, hardware failure, ulceration, recurrent deformity, and radiographic outcomes including union and hardware backout. Reoperation numbers and indications were also collected. Our primary outcome was limb salvage at final follow up. Secondarily, we collected final ambulatory and footwear status. Results: The limb salvage rate was 82% with 10 patients undergoing amputation, which did not vary between groups (p=.99). The primary reasons for amputation were persistent infection (4 of 10) and nonunion (4 of 10). Thirteen (24%) patients developed an infection. The median number of reoperations per patient was 1 (IQR 0-2) with the patients who underwent amputation undergoing a median of 2 (IQR 2-4) reoperations. The rate of union was 54%, occurring at a median of 26.5 (IQR 12-47) months. 44% (4/9) of patients in the external fixation group had a preoperative ulceration versus 19% (9/47) of the patients in the internal fixation group (p=.19). Preoperative ulceration was not a risk factor for amputation. Forty-two (75%) patients were ambulatory at final follow up. Conclusion: We report on the single largest series of Charcot patients undergoing hindfoot and ankle arthrodesis. The surgical management of this population has a high rate of complications with infection and reoperation being common. Despite a high nonunion rate most patients are able to ambulate in a brace or orthotic. Limb salvage can be expected with either internal or external fixation techniques.